Concurrent Infection of the Human Brain with Multiple Borrelia Species - Golovchenko, Maryna; Opelka, Jakub; Vancova, Marie; Sehadova, Hana; Kralikova, Veronika; Dobias, Martin; Raska, Milan; Krupka, Michal; Sloupenska, Kristyna; Rudenko, Natalie (International journal of molecular sciences, 2023)
Lyme disease (LD) spirochetes are well known to be able to disseminate into the tissues of infected hosts, including humans. The diverse strategies used by spirochetes to avoid the host immune system and persist in the host include active immune suppression, induction of immune tolerance, phase and antigenic variation, intracellular seclusion, changing of morphological and physiological state in varying environments, formation of biofilms and persistent forms, and, importantly, incursion into immune-privileged sites such as the brain. Invasion of immune-privileged sites allows the spirochetes to not only escape from the host immune system but can also reduce the efficacy of antibiotic therapy. Here we present a case of the detection of spirochetal DNA in multiple loci in a LD patient's post-mortem brain. The presence of co-infection with Borrelia burgdorferi sensu stricto and Borrelia garinii in this LD patient's brain was confirmed by PCR. Even though both spirochete species were simultaneously present in human brain tissue, the brain regions where the two species were detected were different and non-overlapping. The presence of atypical spirochete morphology was noted by immunohistochemistry of the brain samples. Atypical morphology was also found in the tissues of experimentally infected mice, which were used as a control.
Keywords: lymeská nemoc; human brain; Borrelia burgdorferi Group; Humans; Borrelia garinii; molecular detection; lidé; immunohistochemistry; Borrelia burgdorferi; Lyme disease; Borrelia burgdorferi komplex; Brain; Lyme Disease; persistence; co-infection; mozek; neuroborreliosis; Borrelia